Treg-selective IL-2 starvation synergizes with CD40 activation to sustain durable responses in lymphoma models - Alexandar Tzankov; Nicole Joller; Onur Boyman; Anne Müller; Kristin Stirm; Peter Leary; Daria Wüst; Dominique Stark; Ufuk Karakus (Journal for ImmunoTherapy of Cancer, 2023)
Background Roughly half of all diffuse large B-cell lymphomas (DLBCLs) are infiltrated by large numbers of regulatory T-cells (Tregs). Although the presence of ‘effector’ Tregs in particular is associated with an inferior prognosis in patients on standard rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) immunochemotherapy, the role of this cell type during lymphoma initiation and progression is poorly understood.Methods Here, we use tissue microarrays containing prospectively collected DLBCL patient specimens, as well as data from publicly available cohorts to explore the mutational landscape of Treg-infiltrated DLBCL. We further take advantage of a model of MYC-driven lymphoma to mechanistically dissect the contribution of Tregs to lymphoma pathogenesis and to develop a strategy of Treg-selective interleukin-2 (IL-2) starvation to improve immune control of MYC-driven lymphoma.Results We find that all genetic DLBCL subtypes, except for one characterized by co-occurring MYD88/CD79 mutations, are heavily infiltrated by Tregs. Spectral flow cytometry and scRNA-sequencing reveal the robust expression of functional and immunosuppressive markers on Tregs infiltrating MYC-driven lymphomas; notably, we find that intratumoral Tregs arise due to local conversion from naïve CD4+ precursors on tumor contact. Treg ablation in Foxp3iDTR mice, or by antibody-mediated Treg-selective blockade of IL-2 signaling, strongly reduces the lymphoma burden. We identify lymphoma B-cells as a major source of IL-2, and show that the effects of Treg depletion are reversed by the simultaneous depletion of Foxp3-negative CD4+ T-cells, but not CD8+ T-cells or natural killer (NK) cells. The inhibition of ATP hydrolyzation and adenosine production by Tregs at least partly phenocopies the effects of Treg depletion. Treg depletion further synergizes with pro-apoptotic CD40 activation to sustain durable responses.Conclusion The combined data implicate Tregs as a potential therapeutic target in DLBCL, especially in combination with other immunotherapies.